THE ADDITION EFFECT OF CATFISH (Pangasius hipophthalmus) SURIMI ON DONUT PROCESSING TOWARDS CONSUMEN ACCEPTANCE - Mardianto Hidayat; N. Ira Sari; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research aims to understand the addition effect of catfis surimi on donut towards consumen acceptance and to invent appropriate catfish surimi formula in donut processing. The method used was experimen method that was donut processing with addition catfish surimi with 0%, 5%, 10% and 15%. Based from consumen acceptance rate towards donut with catfish surimi addition showed that D0 treatment was favor with 97,19%, D1 was 97,50%, D2 was 98,12% and D3 was 98,44%. Best donut formulation was D3 with organoleptic value of appearance, taste, texture, and aroma was (3,26), (3,63), (3,65), and (3,68) respectively. Based on the parameters that can be concluded that the treatment is best viewed from the organoleptic contained in D3 treatment (addition of surimi 15%) with such value 3,26 (criteria golden yellow color), flavor 3,63 (criteria feels a bit sweet), texture 3,65 (criteria soft and slightly crunchy), and aroma 3,68 (criteria does not smell the stench of fish). And the value of water content and the proximate best fat content contained in D0 treatment (without surimi) (17,87% and 18,22%) and the best protein content contained in D3 treatment (addition of surimi 15%) (10,28%).keywords: catfish, surimi and donut.